Placas tectônicas – vulcão - Lourenço , Daniela Santana; Lourdes , Dayane Freitas de; Dan , Edircelia Matos; Cruz , Florisvaldo Gonçalves da; Dan , Marlene Amaral de Matos; Carraro, Márcia Regina Simpioni (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
>>> ver pdf